EFFECT OF TEMPERATURE ON THE EXTRACTION OF BIOACTIVE COMPONENTS OF PALM KERNEL (ELAEIS GUINENSIS) OIL EXTRACTS - OLADIPE, TUNMISE; Owoleke, Veronica A.; Adegbegi, Ademuyiwa J.; Taiwo, Abayomi A.; Ibiyemi, David A.; Makinwa, Funmilayo O.; Oludare, Tayo T.; Arudi, Gloria A.; Ekeyi, Yusuf; Salawudeen, Shuaibu; Dada, Gloria (FUDMA Journal of Sciences, 2025)
Palm kernel (Elaeis guinensis) oil (PKO), which is derived from the seeds of the oil palm tree, has been traditionally used in various cultures for its potential health benefits. This study investigated the effects of temperature (High >100°C and low <50°C) on extraction of the bioactive components of Palm Kernel oil extracts. Following the extraction of the hot-pressed palm kernel oil (HPPKO) and cold-pressed palm kernel oil (CPPKO), the physicochemical properties, GC-MS profiling and FTIR analysis of the extracts were carried out. The results showed that HPPKO extract has a significantly p<0.05 higher density, acid value, saponification, pH and peroxide value compared with the CPPKO extract. The GC-MS analysis identified twelve bioactive compounds in the HPPKO with 9,12-Octadecadienoic acid methyl ester, (E, E)- as the highest percentage (48.19%) compound, however, only seven bioactive compounds were found in the CPPKO, with 11-Octadecenoic acid, methyl ester having the highest percentage composition (46.45%). The FTIR analysis also revealed the extracts contained compounds with alcohol, carboxylic acids, amines, amides, aromatic compounds, long aliphatic chain, ethers, ketone, aldehyde side chains. In conclusion, the study revealed that both hot-pressed and cold-pressed palm kernel oil extracts contained compounds with potential pharmacological activity for the management of pathological conditions, however, the chemical and bioactive properties of these extracts significantly depend on their extraction temperature.